The effect of Conditioned playing Exercises On Developing Passing And Heading In Youth Footballers aged (17 – 18) Years Old - Hussein, Raad (Journal of Physical Education, 2016)
The problem of research lies in weaknesses in passing and heading skills for youth soccer players during matches. The aim of the research was to identify the effect of conditioned playing exercises on the development of passing and heading skills in youth soccer players. The researcher hypothesized positive effect of conditioned playing exercises on the development of passing and heading skills in youth soccer players aged (17-18) years. The researcher used the experimental method. The subjects were (20) players divided randomly into two equal groups. the researcher concluded that conditioned playing exercises have positive effect on developing passing and heading in youth soccer players. Finally he recommended using these exercises during training sessions.